The Implementation of Village Financial Management Principles in Escalating Indeks Desa Membangun (IDM) Level for Villages: Learning from The Jati Village, Tuban - Zuhda Mila Fitriana; Nurjanti Takarini; Endang Iryanti; Anajeng Esri Edhi Mahanani (Nusantara Science and Technology Proceedings, 2021)
The Indonesia Government initiates the SDGs' strengthening focus as realizing the Nawacita notion starting from villages. It aims to develop villages under the principles of sustainability in several sectors, such as Economy, Ecology, and Culture. The fundamental aims of this focus are to support the villages’ welfare and share an equal level of development. In the end, villages will be the threshold of community changes toward the self-governing community ideas. To support this, the Indonesian government through the Ministry of Village, Development of Disadvantaged Regions, and Transmigration regulate the priority for the village's financial focus in Ministerial Decree No.7 the Year 2021. It also regulates some principles to be obeyed by the village government in designing village regulations or policies regarding the issue of village finances, development plans, and supervisory actions. It is arguable as to whether this regulation has affected the villages to escalate their level of Indeks Desa Membangun (IDM). Applying the legal research methods by using laws as the sources of research, combined with an empirical and conceptual approach, this paper discusses the ideal principles of the financial management system which help the villages to raise their IDM level. Three discussion covers 1. The authority owned by villages in managing its fund sources, 2. The principles of the village financial management, and 3. The experience of Jati Village, Tuban, East Java.